2015
DOI: 10.1111/jce.12602
|View full text |Cite
|
Sign up to set email alerts
|

Five‐Year Outcomes of Catheter Ablation in Patients with Atrial Fibrillation and Left Ventricular Systolic Dysfunction

Abstract: Recurrence rates of AF in patients with SHF after ablation are common at 5 years with an anticipated ongoing increase. Long-term AF-related comorbidities tended to be less in the AF ablation group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 22 publications
6
46
0
Order By: Relevance
“…[16][17][18] Additionally, Ullah et al reported lower incidences of stroke and death among patients in SR following AF ablation, while Bunch et al reported long-term reductions in mortality and hospitalization for heart failure following the performance of ablation, compared with outcomes with medical therapy; this finding in particular warrants further attention and testing in prospective studies. 31,34 In fact, similar findings were also more recently reported by Di Biase et al, in terms of mortality reduction with ablation as compared with the use of amiodarone for the treatment of CHF patients. 60 Overall, four short-term RCTs have been performed on a limited population.…”
Section: -59supporting
confidence: 75%
See 2 more Smart Citations
“…[16][17][18] Additionally, Ullah et al reported lower incidences of stroke and death among patients in SR following AF ablation, while Bunch et al reported long-term reductions in mortality and hospitalization for heart failure following the performance of ablation, compared with outcomes with medical therapy; this finding in particular warrants further attention and testing in prospective studies. 31,34 In fact, similar findings were also more recently reported by Di Biase et al, in terms of mortality reduction with ablation as compared with the use of amiodarone for the treatment of CHF patients. 60 Overall, four short-term RCTs have been performed on a limited population.…”
Section: -59supporting
confidence: 75%
“…In general, the advanced structural and electrical atrial remodeling characteristic of these patients seems not to impact the final outcome of ablation, although it is frequently associated with the need for multiple procedures to maintain SR. 4 Concerning long-term follow-up, six studies focused on late outcome (i.e., of more than two years) following AF ablation, finding that despite lower efficacy after a single procedure (around 30-50%), the overall efficacy including repeated procedures was ultimately higher, at 70% to 80%. 21,26,28,[31][32][33] Interestingly, despite more procedures being performed per patient in these cases, the complication rates were similar to those in previous studies, mainly due to the use of improved technologies and procedural amendments, such as performing ablation under uninterrupted anticoagulation.…”
Section: -59supporting
confidence: 63%
See 1 more Smart Citation
“…However, late recurrences are common and associated with more advanced atrial substrate associated with structural heart disease. [436][437][438][439][440][441][442][443][444][445][446] It is in this context that it is important to consider the various types of underlying atrial cardiomyopathy and how they may affect ablation outcomes. This is timely, as it has recently been observed that lone AF is a rapidly disappearing entity as we recognize conditions such as sleep apnoea, obesity, endurance exercise etc.…”
Section: Ablation Of Atrial Tachyarrhythmiamentioning
confidence: 99%
“…113,433 Numerous studies have evaluated the efficacy of catheter ablation of both paroxysmal and persistent atrial fibrillation with significant impairment of systolic function. 437,[466][467][468][469][470][471][472][473] The weight of evidence is that sinus rhythm can be successfully achieved in 50 -80% of patients although repeat procedures are common and follow-up periods are usually not more than 12 months. Successful ablation has been associated with significant improvements in ejection fraction and reduction in atrial size in the majority of studies.…”
Section: Age and Atrial Fibrillation Ablationmentioning
confidence: 99%